Evolution Characteristics and Mechanism of the Load/Unload Response Ratio Based on Strain Observation Before the Jiuzhaigou MS7.0 Earthquake - Yue, Chong; Ji, Ping; Wang, Yali; Yu, Huaizhong; Cui, Jin; Yu, Chen; Ma, Yuchuan (Frontiers in Earth Science, 2022)
Strain observation is the most intuitive observation equipment to monitor stress change in the crust. The strain equipment near the epicenter area of the Jiuzhaigou earthquake (JZGEQ) provides a lot of reliable pre-seismic and post-seismic data for the study of stress change. In this paper, the load/unload response ratio (LURR) method is used to study the stress state of rocks by calculating ratio of strain observation during the loading phase and unloading phase. Results show that the LURR method based on strain observation is an effective method to describe the dynamic change of the constitutive relationship of the rocks in the crust. Different from the strain observation, LURR anomaly evolution process is more continuous regardless of time series curve or spatial and temporal distribution characteristics. The LURR curves of different stations begin to increase above 1.0 gradually since six months to one year prior to the occurrence of the JZGEQ, reaching the maximum value in one to three months before the JZGEQ, and subsequently return to a low level. The maximum value of the LURR anomalies decreases with the distance from the epicenters. At the same time, the spatial and temporal evolution characteristics of LURR anomalies show us the process of "extension – enhance - weaken" in the epicenter of the JZGEQ and its peripheral area prior to the earthquake. The concentration areas of LURR anomalies above are all distributed in the pre-seismic normal stress loading zone, which indicate that the faults are in the process of decoupling, and microfracture may exists in the stage of rock dilatancy.